2018
DOI: 10.1155/2018/5296410
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fe3O4@Chitosan Carbon Microbeads: Removal of Doxycycline from Aqueous Solutions through a Fixed Bed via Sequential Adsorption and Heterogeneous Fenton-Like Regeneration

Abstract: The adsorptive removal of antibiotics from aqueous solutions is recognized as the most suitable approach due to its easy operation, low cost, nontoxic properties, and high efficiency. However, the conventional regeneration of saturated adsorbents is an expensive and time-consuming process in practical wastewater treatment. Herein, a scalable adsorbent of magnetic Fe3O4@chitosan carbon microbeads (MCM) was successfully prepared by embedding Fe3O4 nanoparticles into chitosan hydrogel via an alkali gelation-therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…Another study used the same treatment, to remove Doxycycline (antibiotic) using Magnetic Fe3O4@chitosan carbon microbeads [77]. The results showed that the adsorption capacity increased as the pH value increased, from 2 to 11.…”
Section: Continuous Flow Systemmentioning
confidence: 99%
“…Another study used the same treatment, to remove Doxycycline (antibiotic) using Magnetic Fe3O4@chitosan carbon microbeads [77]. The results showed that the adsorption capacity increased as the pH value increased, from 2 to 11.…”
Section: Continuous Flow Systemmentioning
confidence: 99%
“…14,16 Physical modifications featuring conversion of chitosan into various forms such as flake, sponge, bead and membrane have also been carried out to enhance the stability of chitosan. 10 Among all these physical forms of chitosan and chitosan-based adsorbent materials, the bead form has gained more attention recently because of its improved mechanical and chemical stability [17][18][19][20][21] on one hand, and adequate separation and heterogeneity of the adsorbent from solution on the other hand. 14 In this regard, modification of chitosan-activated charcoal composite into a bead could also offer assistance in achieving better stability for chitosan, as this may also include preventing the leaching of a functional component of activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…El rendimiento de las columnas de lecho fijo se analiza por medio de curvas de avance "S" (ruptura o agotamiento), donde es representado por medio de la concentración del efluente en un intervalo de tiempo establecido (Patel, 2019). En la Figura 6, se representa una curva de avance (C/C0 ~ frente al tiempo), MTZ indica la zona de saturación, el punto de ruptura (tb) y punto de saturación (te) acontece cuando C/C0 = 0.05 y C/C0 = 0.9, respectivamente (Bai et al, 2018;Tan & Hameed, 2017).…”
Section: Lecho Fijounclassified